A case of hereditary angioedema with recurrent arthritis, erythema marginatum-like rash and chest pain - Ergin, Hacer; Başkan, Merve; Akalin, Necdet; Gürses, Dolunay (The Turkish Journal of Pediatrics, 2003)
Hereditary angioedema (HAE) results from a congenital deficiency of C1 inhibitor and is characterized by submucosal and subcutaneous edema of skin, larynx and abdomen. Occasional reports have appeared linking HAE with autoimmune diseases. We report a case of HAE presenting recurrent nondeforming polyarthritis, erythema marginatum-like rash and chest pain. There were no significant radiographic joint changes. Serologic tests for rheumatologic and autoimmune diseases were negative. After danazol treatment, physical examination and laboratory findings were normal over five years. We suggest that pediatricians should be aware of this rare disease and treat patients accordingly.